(untitled) (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Juvenile stage plants contribute significant proportion of forest biomass and carbon depending on successional stage. Thus, the juvenile plants play a significant role in forest ecosystem and they cannot be neglected while estimating the total carbon stocks of the forest. Therefore this study was carried out develop juvenile biomass models. We measured diameter at 10 cm above ground level (D), total height (H) and total biomass (W) of Alnus nepalensis juveniles. We used least square regression technique to develop biomass models. The models were estimated using “library(minpack. lm)” in R. The estimated models were evaluated by using numerical fit statistics and graphical analyses. Among 136 different models tested, the model of the form: Wi= β0+β1(D2H) with explanatory variable D2H accounted for the largest proportion of biomass variations (R2adj = 0.97; RMSE = 42.34g; AIC=406.8.7) for individual Alnus nepalensis juveniles, and showed relatively better graphical appearance and biological logic. DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10812 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 47-60